Building Their Own Connections: University EFL Learners’ Culture Learning Through a Language MOOC on Source Culture - Qian Liu; Qi Chen; Yingqi Zhao; Ying Li (SAGE Open)
This study examined how Chinese university English as a foreign language (EFL) students engaged in a language massive open online course (LMOOC) on source culture to meet their learning needs. Learning analytics data from 818 course participants revealed a funnel-shaped pattern of participation, with a significant decline in video-watching and discussion forum participation occurring before the midpoint of the course. However, the quality of student contributions remained stable, as no significant decline was observed in the length or syntactic complexity of discussion board posts. To further investigate these engagement behaviors, we conducted interviews with 47 participants and identified three types of learners with distinct learning objectives: culture-learning-oriented learners, language-learning-oriented learners, and culture- and language-integrated learning-oriented learners. Our findings highlight the selective nature of learner engagement in LMOOC activities, where learners exercised agency in choosing how to interact with course resources. Despite not always adhering to traditional course completion patterns, they continuously engaged in deep reflection on language and culture learning, which led to extended learning practices and increased awareness of cultural identity both within and beyond the LMOOC. This study offers practical implications for LMOOC designers and addresses the need for EFL educators to reassess the goals and methods of culture teaching, promoting reflective engagement in culture learning in today’s globalized, technology-driven world.